Nucleon flavor asymmetry in a statistical quark model - Trevisan, L. A.; Mirez, C.; Tomio, Lauro; Frederico, T. (Elsevier B.V., 2007)
A statistical model of linear-confined quarks is applied to obtain the flavor asymmetry of the nucleon sea. The model parametrization is fixed by the experimental available data, where a temperature parameter is used to fit the Gottfried sum rule violation. Results are presented for the ratios of light quark and antiquark distributions, d/u and (d) over bar/(u) over bar.